Effect of Drying Methods on the Total Phenolic of Maman Plant (Cleome gynandra L.) from Riau - Fauzan, Muhamad; Roslim, Dewi Indriyani; Safarrida, Anna; Herman, Herman; Lestari, Wahyu (Jurnal Biologi Tropis, 2024)
Maman plant (Cleome gynandra L.) is an underutilised leafy vegetable that has a high nutritive value and contains phenolic compounds that are essential in reducing or preventing the occurrence of chronic and infectious diseases. In this study, we investigate the effect of drying methods on the total phenolic content of maman plant from Riau. The drying treatment process for maman leafs was tried using three methods: room air-dried without sunlight exposure at 21-24oC for seven days, freeze-dried at -40oC for four days, and oven-drying at 40oC for three days. Freeze-dried maman leafs exhibited significantly (p < 0.05) higher total phenolics (5,90 mgGAE/g) than those dried using other methods, followed by oven-dried (5,14 mgGAE/g) and room-air dried (4,50 mgGAE/g). Drying maman leaves for further research is recommended using the freeze-dried method to obtain optimal phytochemical content.